Access to drinking water and reduction of acute diarrheal diseases in rural populations Puno-Peru - Inquilla-Mamani, Juan; Quispe-Borda, Wenceslao; Apaza-Ticona, Jorge; Inquilla-Arcata, Fernando; Calatayud-Mendoza, Alfredo Pelayo; Chaiña-Chura, Fermin Francisco; Velásquez-Sagua , Héctor Luciano; Mamani-Flores, Adderly (Journal of Posthumanism, 2025)
This quasi-experimental study evaluated the impact of access to drinking water and sanitation on the reduction of acute diarrheal diseases (ADD) in rural communities of Puno, Peru, using a longitudinal design with the Differences in Differences (DID) technique and Probit models to estimate the impact coefficients. The sample included 100% of the population that used water services (n=179 households) and non-users (n=170 households) of water services in the district of Ilave. The results showed that households with access to drinking water had a significantly lower prevalence of EDA (43.0%) compared to those without access (60.5%), with an estimated difference of -17.5 percentage points (p<0.01). Analysis using Probit models revealed that access to drinking water reduced the probability of EDA by 17.9%, an effect that was statistically significant (β=-0.175; p<0.01). These findings confirm that access to drinking water and sanitation constitutes a key protective factor against EDA in rural contexts, highlighting the importance of implementing comprehensive interventions that combine water infrastructure with the promotion of hygienic practices. The study provides robust evidence to guide public policies on environmental health, particularly in regions with limited access to basic services, and underscores the need to prioritize these interventions as an effective strategy to reduce the burden of preventable diseases in vulnerable populations, thus contributing to the achievement of the Sustainable Development Goals.